PENGARUH MODEL PROJECT-BASED LEARNING TERHADAP KEMAMPUAN MENULIS KARYA ILMIAH PADA SISWA KELAS XI SMA NEGERI 3 PEMATANGSIANTAR - Gultom, Sopanro; Saragih, Vita Riahni; Silitonga, Immanuel Doclas Belmondo; Tambunan, Marlina Agkris; Siregar, Junifer (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Project-Based Learning model on students' scientific writing ability in class XI-1 of SMA Negeri 3 Pematangsiantar. The background of the study was the students' difficulty in organizing scientific paper structure, developing ideas, using formal academic language, and applying spelling and punctuation accurately. This research used a quantitative experimental approach with a one-group pre-test and post-test design. The sample consisted of 36 students selected through purposive sampling. The research instrument was a scientific paper writing test assessed through five aspects: structure and systematics, content development and material accuracy, use of standard language, spelling and punctuation accuracy, and writing neatness. Data were analyzed by calculating the mean score, percentage of each assessment aspect, and normalized gain (N-Gain). The results showed that the average pre-test score was 67.92, while the average post-test score increased to 84.44. The average N-Gain score was 0.49356, categorized as moderate, and the N-Gain percentage was 49.35596%, categorized as less effective. These findings indicate that Project-Based Learning has a positive effect on students' scientific writing ability, although its implementation still needs to be optimized through better time management, intensive teacher guidance, clear writing examples, and continuous writing practice.